Unfulfilled Promises: Analyzing Delayed Strata Title Certificates Under Indonesia’s Apartment Law in Surabaya - Pebriananta, Rifki; Lesmana, Rizki Febrian; Zulfikar, Zudan Ahmad (Indonesian Journal of Agrarian Law, 2025)
The delay in issuing Certificate of Ownership for Apartment Units (SHMSRS) by apartment developers in Surabaya has become a chronic issue harming consumers. This study analyzes developers' obligations under Law No. 20 of 2011 on Apartment Buildings and legal remedies available for apartment owners. The research employs a normative juridical approach with case studies on Surabaya apartment projects experiencing SHMSRS delays. Findings indicate that developers are legally required to issue SHMSRS after construction completion and full payment, but enforcement remains weak due to bureaucratic hurdles, developers' financial constraints, and lack of oversight. Apartment owners can pursue litigation (civil lawsuits or class actions) or non-litigation avenues (via Consumer Dispute Resolution Agency/BPSK, Financial Services Authority/OJK, or related agencies). Strengthening inter-agency coordination, streamlining procedures, and empowering consumers are essential to ensure developer compliance.